Empirical Analysis of Rural Local Government in Bangladesh: Problems and Way Out - Amin, Ruhul (PT. Riset Press International, 2023)
The government might be national, provincial, state, or municipal. Local government refers to the administration of a locality or small community, such as a village, town, or city, by the body representing the local population, with a considerable level of autonomy, earning at least a part of its income from local taxes, and spending the proceeds on services. One of the most important preconditions for the growth of local governments is the democratization of governmental management. The breaking up of ownership monopolies fosters the growth of economies with many structures. The establishment of government powers that are both durable and effective is required in order to generate adequate conditions for business. These conditions must encompass a wide variety of factors, including favorable rules of play, the protection of ownership rights, and so on. The study utilizes both primary and secondary information and also make use of both quantitative and qualitative data. Quantitative data was collected through a set of semi-structured questionnaire & interviewing of different stakeholders in local government. Under Qualitative data, information was collected through survey method and KII. Besides, the secondary data was collected through the books, journals, reports and newspaper. The number of total respondents was 50. Finally, Descriptive, analytical and empirical methods was use to analyses the data. The study will help in understanding the transformation of local government in Bangladesh and in future measures to strengthen it.